Platform-Independent Methodology for Partial Reconfiguration - Koch, Dirk; Teich, Jürgen (Proceedings of the 2004 ACM conference Computing Frountiers, 2004)
In this paper we present a novel methodology for partial (re-)configuration that can be used for most bitstream configured hardware (HW). In particular low priced and not for partial reconfiguration designed devices can be used by our technique. Furthermore, the methodology is platform independent and requires neither specialized HW synthesis tools nor a documented bitstream. We manage configuration data by extracting and compressing (sub-) module data from complete bitstreams. Experiments demonstrated that this extracted bitstreams could be compressed down by orders of the primary bitstream size for some submpdules.
UnivIS-Import:2015-04-16:Pub.2004.tech.IMMD.inform.platfo
Keywords: Bitstream Extraction; Configuration Compression; Partial Reconfiguration